Augmin-dependent microtubule self-organization drives kinetochore fiber maturation in mammals - Ana C. Almeida; Joana Soares-de-Oliveira; Danica Drpic; Liam P. Cheeseman; Joana Damas; Harris A. Lewin; Denis M. Larkin; Paulo Aguiar; António J. Pereira; Helder Maiato (Cell Reports, 2022)
Summary: Chromosome segregation in mammals relies on the maturation of a thick bundle of kinetochore-attached microtubules known as k-fiber. How k-fibers mature from initial kinetochore microtubule attachments remains a fundamental question. By combining molecular perturbations and phenotypic analyses in Indian muntjac fibroblasts containing the lowest known diploid chromosome number in mammals (2N = 6) and distinctively large kinetochores, with fixed/live-cell super-resolution coherent-hybrid stimulated emission depletion (CH-STED) nanoscopy and laser microsurgery, we demonstrate a key role for augmin in kinetochore microtubule self-organization and maturation, regardless of pioneer centrosomal microtubules. In doing so, augmin promotes kinetochore and interpolar microtubule turnover and poleward flux. Tracking of microtubule growth events within individual k-fibers reveals a wide angular dispersion, consistent with augmin-mediated branched microtubule nucleation. Augmin depletion reduces the frequency of kinetochore microtubule growth events and hampers efficient repair after acute k-fiber injury by laser microsurgery. Together, these findings underscore the contribution of augmin-mediated microtubule amplification for k-fiber self-organization and maturation in mammals.